Stokes' Law Approach to Slag Formation Process to Increase the Effectiveness of Cleaning Metal Liquids in Cast Iron Smelting Process - Muhammad Rizki Gorbyandi Nadi; Cecep Ruskandi; Ari Siswanto; Gita Novian Hermana (Journal of Physics and Its Applications, 2022)
The purpose of this study was to increase the effectiveness of slag cleaning in the cast iron smelting process using an induction furnace. This study resulted in the calculation of the terminal velocity of the slag emerging to the surface of the induction furnace based on Stokes' Law approach for each slag that appears during the cast iron smelting process. For each cast iron casting, three samples were taken based on the fastest time on the very light slag, the slag’s time for the heaviest slag, and the extreme time for comparison. The results of each sample are tested for characterization such as shape, size, and chemical composition of each sample which are then adjusted to the calculations that have been made. The characterization was analyzed using X-ray diffraction, scanning electroscope, and energy dispersive spectroscopy microanalysis. The results show that the Stokes law approach to predict the slag reaching the surface gets the appropriate result that all the slag reaches the surface at time t = 230 s. The slag that appears at time t = 300 s is the slag formed due to the interaction of the liquid with the surface which is not the slag that occurs from the raw material used. This study succeeded in minimizing the formation of slag in each casting of cast iron using an induction furnace.